Impact of value-based transformational leadership in privatizing government institutions in a developing economy: a case study / Mohammed-Aminu Sanda - Sanda, Mohammed-Aminu (Institute of Business Excellence and UPENA, 2010)
The purpose of this study was to explore the kind of leadership that could infect positive changes in the work environments of government research organizations undergoing privatization in most developing countries in order to enhance the commercialisation of their production activities. An interpretive analytic framework was used as an appropriate platform to build a qualitative design. Qualitative data was collected through taped-recorded interviews with seventeen senior staff members identified as key actors in the organization’s privatization processes, and analysed using an interpretive description qualitative approach. The results showed that the organization’s managers used charismatic and values-based leadership approaches during the transition period of commercialisation process and was viewed by their subordinates as leaders who were true to their own values and who also went on to help those they led to articulate what they valued. It was concluded that an amalgamation of transformational and value-based styles of leadership approach could be used by managers of government agencies in most developing countries to infect positive changes in their work environments when managing the privatization of their organizations. The study has shown that value-based transformational leadership could be used by managers of challenged government research and development organizations in most developed countries to infect positive changes in their work environments and which could help facilitate their efforts towards the privatization of their organizations’ activities.